1994
DOI: 10.1113/jphysiol.1994.sp020204
|View full text |Cite
|
Sign up to set email alerts
|

Cation‐dependent gating of the hyperpolarization‐activated cation current in the rabbit sino‐atrial node cells.

Abstract: 1. The gating properties of the hyperpolarization-activated cation current (If or either by prolonging the duration or by increasing the amplitude of the preceding hyperpolarization in both Na+ and Li' solutions.5. The If was first activated by hyperpolarizing the membrane to -110 mV, and then deactivated by depolarization. The inward tail current at -50 mV showed a single exponential decay. At more positive potentials, the shoulder of the outward tail currents became more evident and the rate of the final d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 40 publications
9
30
0
Order By: Relevance
“…Extrapolation of the measured I f values yielded an x-intercept of 0.21 indicating that I f was eliminated despite the fact that driving forces were inward for both Na ϩ and K ϩ . This behavior has also been reported in studies of native I f (8,(27)(28)(29). The corresponding concentrations determined at the x-intercept were 3.3 mM K ϩ and 136.7 mM Na ϩ , which compares to 3.8 mM K ϩ and 136.3 mM Na ϩ determined at Ϫ65 mV (Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Extrapolation of the measured I f values yielded an x-intercept of 0.21 indicating that I f was eliminated despite the fact that driving forces were inward for both Na ϩ and K ϩ . This behavior has also been reported in studies of native I f (8,(27)(28)(29). The corresponding concentrations determined at the x-intercept were 3.3 mM K ϩ and 136.7 mM Na ϩ , which compares to 3.8 mM K ϩ and 136.3 mM Na ϩ determined at Ϫ65 mV (Fig.…”
Section: Resultssupporting
confidence: 85%
“…Previous studies of I f in sensory neurons, apical dendrites of hippocampal CA1 pyramidal neurons, and myocytes from the sinoatrial node have shown that deactivation was affected by relatively large changes in external cations (28,40,41). Despite concurrent changes in I f amplitude that reflected interactions of Na ϩ and K ϩ in the pore, a separate mechanism was proposed for the effects of cations on I f deactivation that involve an external binding site (28). The primary argument in favor of an external binding site was that only K ϩ could be present in the pore during measurements of outward tail currents because Na ϩ was not present in the intracellular solution and thus would have left the pore almost instantly upon depolarization.…”
Section: Discussionmentioning
confidence: 94%
“…The intriguingly similar activation kinetics of I f in myocytes of the sinoatrial node and cardiac Purkinje fibers (28)(29)(30) and of hHCN4 certainly support this conclusion. However, the activation threshold of I f in cardiac Purkinje fiber is distinctively more negative than in the sinoatrial node (29,31).…”
Section: Discussionmentioning
confidence: 71%
“…ϩ is permeant through h-channels (Ho et al, 1994;Maruoka et al, 1994) but does not stimulate the Na ϩ -K ϩ pump as strongly as Na ϩ ions (Foley, 1984;Chen et al, 1989;Rasmussen et al, 1989). As shown in Figure 6 Aa, when extracellular Na ϩ ions were substituted with Li ϩ ions, the apparent I h was depressed or enhanced depending on the amplitude of test pulses applied at Ϫ50 mV (n ϭ 5).…”
Section: LImentioning
confidence: 94%